ANALISIS DOKTRIN DALAM FILM "LUCA" KARYA CASAROSA - Anastasia, Happy (ELOQUENCE : Journal of Foreign Language, 2023)
Background: Films seen from the element of doctrine are very interesting to be used as positive lessons, because every action can have consequences for choices in attitude. Purpose: This study aims to observe the doctrine in the film "Luca" by Enrico Casarosa, so that it can be known the consequences must be accepted by Luca as the main character, the attitude that must be carried out in response to the doctrine. Method: This research is a literature research. The primary data source was obtained by Casarosa's film "Luca" published in 2021.  The data analysis method uses content-based qualitative analysis of dialogue words, sentences, images, cuts, scenes, paragraphs, and descriptive film narratives as well as the responses of the main character "Luca" who have elements of doctrination. Data analysis techniques are carried out through three stages: data reduction, data display, and conclusion pulling/verification Results and Discussion: The results of this study show that there is a doctrine in the film "Luca" by Casarosa. Doctrine against the main character, Luca: Among them are 1) obedience, which is marked by running into hiding; he must not have contact with man; It is not allowed to talk, discuss, and even approach the surface of the sea. As a consequence, if Luca does not comply, he will be captured and killed by humans. 2) Freedom, which is characterized by humans having their own vehicle in life, does not need anyone without pressure. As a consequence, if he does not follow Alberto's character, he will not get freedom, cannot adventure in the human world, and will still feel afraid of everything. 3) Continue to learn, create and innovate, this is indicated by the existence of a telescope that can observe distant objects seen closely; You can travel in the universe and galaxies only through small tools such as telescopes. As a consequence, if he hadn't followed Giulia, he would never have had the experience of a telescope adventure. This tells us about the importance of going to school. Conclusions and Implications: The film "Luca", Casarosa inserts several doctrines to serve as lessons such as: 1) Whenever we see danger or murderers, we need to run to hide. Unless, we will be killed. 2) Whenever we have worries or fears in mind, we need to encourage them all and build our own ways to manage them as a force. Unless, we will continue to feel afraid of facing problems. 3) Dare to learn more, to experience more, to adventure more, especially to the world, universe, and galaxy, then our knowledge will increase. If we just stay and do nothing, we will only continue to be like a frog in a shell. 4) Learn more to increase knowledge, then we will know how to adventure the world and universe. If we do not develop ourselves by learning, then we will only become like people who stutter in knowledge.